Organizational and financial changes in the work of primary health care workers during the COVID-19 pandemic inPoland - Anna Rybarczyk-Szwajkowska; Anna Staszewska; Małgorzata Timler; Izabela Rydlewska-Liszkowska (Nofer Institute of Occupational Medicine, 2021)
Following the outbreak of the COVID-19 pandemic, the objectives of the health care system had to be adapted to the changing circumstances, in order to meet the health needs of patients, but also the expectations of medical workers related to ensuring safe working conditions in the crisis situation. The activities of medical staff are greatly affected by organizational and financial changes in health care systems, which affect both the health care systems all over the world and the functioning of all forms of health care. The article examines the organizational and financial changes resulting from the introduction of regulations affecting the conditions of primary health care (PHC) workers in Poland from the beginning of the COVID-19 pandemic to May 8, 2021. The findings regarding measures taken to ensure the stability of PHC functioning during the pandemic highlight that the public health emergency exposed a significant need to introduce organizational and financial changes in PHC. The changes arising from legislation and good practices of medical, organizational and financial character resulted in health care system modernizations in Poland. It is worth stressing, however, that there is a great need to maintain coherence when implementing organizational and financial changes affecting the fluidity and effectiveness of the actions taken by PHC personnel, and thus their working conditions, when implementing future responses to public health emergencies. Such changes should be based on an analysis of the solutions introduced since the beginning of the pandemic in Poland: these include organizational changes such as housing conditions, organization of work and workplaces, flow of information and way of supplying the patient, and financial changes involving mobilization of additional financial resources. The article presents a list of future research questions that merit consideration when setting problems and priorities: these can be used to guide the introduction of permanent modifications to the functioning of PHC in Poland and to facilitate possible future adaptation in times of emergency. Med Pr. 2021;72(5):591-604